Linguistic anxiety and strategies teaching-learning of pre-service english teachers: Ansiedad lingüística y estrategias de enseñanza-aprendizaje de docentes de inglés en formación profesional - Bravo López, Ashley Milena; Holguín Mora, Itsel Geanina; Bello Piguave, Johanna Elizabeth (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2026)
Language anxiety is a phenomenon that occurs in the teaching and learning of foreign languages, especially in vocational training contexts, affecting communicative skills and, in turn, the application or correct use of teaching strategies. This research was conducted to analyze the relationship between language anxiety and the teaching and learning strategies used in the formation of English teachers at a public university in Manta, Manabí (Ecuador). A mixed methodological approach was adopted, both descriptive and comparative, with a sample of 60 first and final semester students. Data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) (Horwitz et al., 1986) and semi-structured interviews to explore the teaching strategies that influence comfort and confidence in communicating in English. The findings manifested moderate to high anxiety with no significant differences between both semesters, first and last semesters, related to fear of negative evaluation, shyness, and public exposure. Moreover, the best practices found were teamwork, small groups, prior preparation, positive feedback among peers, and digital tools to conduct self-assessment and teacher empathy. Therefore, it is considered that academic experience is not enough to reduce language anxiety, and it is necessary to create emotionally safe environments to build up their self-confidence in oral communication in English.